Legal limits of scientific experiments in Sudanese Law (Comparative Study) - Idries, Fadul Yousif (Journal of Economic, Administrative and Legal Sciences, 2022)
The research aimed at define the concept of scientific experiments in the light of international conventions and to determine the extent of their legal organization and the limitations of conducting them in Sudanese law. The problem of the study lies in the adequacy of the Sudanese law’s regulation of scientific experiments and the controls of conducting them on the human body, to protect the human body from its dangers. The study concluded a number of results, the most important are: There is no law that comprehensively regulates the conduct of scientific experiments in Sudan in a way that protects the person subject to the experiment, with the exception of some texts regulating drug experiments that were contained in the Pharmacy and Poisons Law2009, and the Constitution of Sudan did not prohibit the conduct of scientific experiments; rather, he encouraged it. He recommended the inevitability of the intervention of the Sudanese legislator to organize scientific experiments in special legislation on the guidance of what international agreements have reached. This study recommended the inevitability of the intervention of the Sudanese legislator to organize scientific experiments in special legislation on the guidance of what international agreements have reached, and to set strict controls and restrictions to ensure the necessary respect for the ethics of medical experiments, accompanied by developments that have occurred in medical experiments, and finally the creation of a national information base that is responsible for listing scientific experiments and evaluating their positive and negative results to bring about continuous development in these laws in light of these results.